An experimental study on a novel reclaimed rubber compound for fiber-reinforced seismic isolators. (November 2022) - Cilento, Fabrizia; Losanno, Daniele; Piga, Luigi
Abstract: Classical rubber seismic isolators reinforced with steel shims are generally large, heavy, and expensive so rarely used for housing buildings. In the last few years, different technologies have been investigated and fiber reinforced elastomeric isolators (FREIs) demonstrated to be a promising option. Only by properly combining a lower cost of raw materials including the manufacturing process and an easier installation process can result in a cost-effective solution. In the present study, novel reclaimed-rubber FREIs reinforced with low cost fabrics were designed and manufactured. A reclaimed compound (RC) has been developed resulting in mechanical properties not significantly different from virgin rubber. Mechanical characterization of the RC showed a typical response of soft compound even if with lower tensile deformation capacity. RC adhesion with polyester and nylon fabrics was investigated in order to prevent debonding between different layers. In this regard recycled-rubber FREIs with polyester and nylon fabrics were manufactured and tested in unbonded configuration. The devices showed promising performance and paved the way for the development of low-cost and environmental-friendly seismic isolators for housing buildings.